Terminação de cordeiros alimentados com dieta de alto grão em sistema de confinamento - Leite, Helia Maria de Souza (Universidade Federal Rural do Semi-Árido, 2017)
The objective of the study was to evaluate the effect of different proportions of high-level diets on finishing lambs in feedlot system on performance. However, there is no ingestive and physiological behavior, as well as carcass characteristics, quality physical and chemical characteristics of meat and production costs. For this purpose, whole corn grain associated with the protein-mineral-vitamin supplement was used in three proportions of concentrate: bulky (100%, 80:20 and 60:40%), a concentrated portion of the diet composed of 85 % of whole corn grain and 15% of supplement and bulky portion of Tifton hay). Twentyfour non-castrated males with no defined racial pattern were used with initial weight of 20.9 ± 1.0 kg at the age of 6 months. Weight gain was achieved in the three diets tested from 0.302g / day for 100% diet, 0.254g / day to 80:20 and 0.259g / day for 60:40 Minor rumination time (P≤0.05) in lambs of the treatment based on grain 100% when compared to the lambs of the other treatments. The 100% diet presented higher feed efficiency (EAL) and also more efficient rumination (ERU). Evaluating a temperature of the rumen region, it can be seen that the animals that received a 100% diet showed the variation of the temperature of the reen region, as 80:20 and 60: 40% diets affect nearby temperatures. As evaluated diets contributed to the performance with satisfactory gains, although preferences of use of diet of high grade, these guarantee like basic actions. There was a significant effect on carcass yield. A 100% concentrated diet showed a carcass yield of 47%, while for 80: 20% and 60: 40% diets obtained carcass yield values of 43.5% and 43.4%, respectively. The gastrointestinal content also had an effect, being lower in treatments 100% and 80: 20%. (P> 0.05) in the variables pH, temperature, color, water retention capacity and shear force. The 100% treatment presented a weight loss in cooking as well as superior thiobarbituric acid (TBARS) when compared with other diets. The 100% diet, when compared with other diets, obtained an additional carcass weight of 2.30 kg per animal. The use of the 100% concentrated diet in lamb termination systems is a more viable alternative from a productive and economical point of view
Keywords: Concentrado; Confinamento; Desempenho; Concentrate; Confinement; Performance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA